Rosuvastatin plus fenofibrate in diabetic dyslipidemia: a hospital record based study - Gopal, K. Madhana; Meganathan, M.; Vithiavathi, S.; Shankar, S. Prabhu; Balamurugan, K.; P., Deepa Kameswari (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Cardiovascular diseases (CVD) are the leading cause of death throughout world population each and every year. Focus on dyslipidemia management is urgently required in India to halt the rising tide of CVD. The purpose of diabetic dyslipidemia study is a record based one, to find out the effect of Rosuvastatin plus Fenofibrate, in adult Type 2 diabetes with dyslipidemia, with high TGL/HDL ratio in Lipid profiles, in a tertiary care hospital in the Union territory of Puducherry. Methods: There were 101 patients hospital records were analysed in which male were 45 and females were 56. The various biochemical parameters like serum Total Cholesterol, HDL, LDL, TGL, Non-HDL, TCL/HDL Ratio and TGL/HDL ratio reports were collected before and after 12-weeks of Rosuvastatin 10 mg with Fenofibrate 145 mg combination, for the treatment period once daily for their lipid-lowering therapy. Results: The combination therapies of Rosuvastatin plus Fenofibrate were safe and feasible to achieve more TG goal and proved that has predominately decreased the elevated lipid profiles from the medical resources of our record based study. The use of combination medications of rosuvastatin (10mg) plus Fenofibrate (145mg) is often needed to effectively treat the lipid triad, by the potency of rosuvastatin to lower LDL-C and Fenofibrates effectiveness in lowering TG in treating mixed diabetic dyslipidemia. Conclusions: After Rosuvastatin (10mg) plus Fenofibrate (145mg), the lipid profile data proved that the importance of TGL/HDL ratio apart from the TCL/HDL ratio, for good lipid control in diabetic dyslipidemic patients.